2012
DOI: 10.4028/www.scientific.net/amm.260-261.236
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Secure GOOSE Protocol Using HSM

Abstract: The smart grid is a developing network of transmission lines, equipment, controls and new technologies working together to respond immediately to 21st Century demand for electricity, but the smart grid may also create much new vulnerability if not deployed with the appropriate security controls. In this paper, to evaluate the secure GOOSE message performance, we implemented the IEC 62351-6 MAC mechanism, applied it on F-IED using the IEC 61850 GOOSE stack and the HSM, built the security test environment, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although some existing research works, as explained above, demonstrated attacks against the GOOSE protocol, no research so far has shown a comprehensive vulnerability analysis of the GOOSE communication protocol based on both theoretical claims, as well as experimental simulations. Following the recommendation by Part 6 of IEC 62351 to use the HMAC scheme, the authors in [ 27 ] implemented the SHA256 authentication mechanism for the GOOSE protocol. Our paper studies the inherent vulnerabilities of the GOOSE communication protocol within a substation environment considering with and without the IEC 62351 security standard.…”
Section: Related Workmentioning
confidence: 99%
“…Although some existing research works, as explained above, demonstrated attacks against the GOOSE protocol, no research so far has shown a comprehensive vulnerability analysis of the GOOSE communication protocol based on both theoretical claims, as well as experimental simulations. Following the recommendation by Part 6 of IEC 62351 to use the HMAC scheme, the authors in [ 27 ] implemented the SHA256 authentication mechanism for the GOOSE protocol. Our paper studies the inherent vulnerabilities of the GOOSE communication protocol within a substation environment considering with and without the IEC 62351 security standard.…”
Section: Related Workmentioning
confidence: 99%